Steering Strategy in the Speech of Al’A’rāb (Deliberative Study) (Texas Journal of Philology, Culture and History, 2023)
This study examines one of the aspects of discourse analysis, which is discourse strategies. Because of the importance of the words of the Arabs, and their place in our Arabic language; Where it is considered one of the basic sources that are reliable in setting the grammatical, rhetorical and morphological rules of the language...etc. from the language sciences